ALP Proteksi Hukum Pasien Dalam Pelayanan Kesehatan Di Ruang Opname RSUD Dr. Slamet Garut - Aceng Ali Awaludin; Andhika Lungguh Perceka (STIKes Karsa Husada Garut, 2019)
Legal protection is the right to acquire justice, regularity, provision, usefulness and convenience to the rights of individuals or groups in the eyes of the law. This research discusses the protection of the patient's law when receiving health care services in Dr. Slamet Garut Hospital which is studied at the rules of consumer protection and health legislation with the aim to know how the legal protection Patients and their implementation in healthcare services and fulfilling the rights of patients by health and hospital personnel. Techniques used quantitative descriptive, univariate analysis, sample number 97 respondents, data was taken using a question sheet and the results showed that most of the respondents (66.0%) Patient's legal protection is fulfilled and nearly half the respondent (34.0%) Patient legal protection is not met. There should be a strategy or effort from the hospital to further improve the legal protection aspect of the patient in order to obtain appropriate services to the patient, so that the patient's legal protection can be fully fulfilled.